Correlation of Random Urine Protein Creatinine (P-C) Ratio with 24-Hour Protein Urine in Lupus Nephritis Patients - Y H Aini; A Tjandrawati; N Suraya; Laniyati Hamijoyo (Indonesian Rheumatology Association, 2016)
Background : Systemic lupus erythematosus (SLE) is a systemic autoimmune disease involving multiple organs including kidney and known as lupus nephritis (LN). Lupus nephritis has a poor prognosis after a 10-years onset, more than 25% will be ended by end stage renal disease. There are glomerular and tubulointerstitial tissue damages due to immune complex deposits in LN which is activating inflamation cascade and causing disfunction of glomerular filtration and tubular reabsorption resulting proteinuria. In LN, proteinuria is used to diagnose, to assess the disease activity and to monitor the therapy. The gold standard of proteinuria is 24-hour urine protein examination, but the process ofcollecting in 24 hour urine is difficult, then the result is less accurate and reliable. Another alternative parameter is spot urine protein/creatinine ratio. Several studies have found a positive correlation between spot urine protein/creatinine ratio and 24-hour urine protein levels, but in LN, the results are various.Objective: The aim of this study was analyzing the correlation between spot urine protein/creatinine ratio and 24-hour urine protein in lupus nephritis.Methods: The study was conducted at Dr. Hasan Sadikin Hospital, Bandung, West Java, Indonesia in October 2014 to December 2014. The subjects were 45 patients with lupus nephritis based on the criteria of the American College of Rheumatology. The study analyzedcorrelation through cross-sectional model. Results: The results of Spearman correlation test analysis showed a significantly strong positive correlation between spot urine protein/creatinine ratio and 24-hour urine protein levels in lupus nephritis (rs =0.96; p <0.001). Based on the degree of proteinuria there was a strong positive correlation between spot urine protein/creatinine ratio and 24-hour urine protein levels in lupus nephritis significantly on the degree of protein <1 g/24-h (rs = 0.91; p <0.001) and at 1–3.5 g/24-h (rs = 0.73; p<0.05).Conclusion : There is a significant strong positive correlation between spot urine protein/creatinine ratio and the 24-hour urine protein levels in lupus nephritis, so it is recommended to use spot urine protein/creatinine ratio, as an alternative quantitative examination in lupus nephritis.Keywords: lupus nephritis, 24-hour urine protein, spot urine protein/creatinine ratio